Kajian kualiti air tasik kejuruteraan UKM ke arah mewujudkan kampus lestari dan mesra alam - Othman A. Karim,; Irene Lee Pei Ngo,; Mazlin Mokhtar,; Azami Zaharim, (2006)
Universiti Kebangsaan Malaysia is working towards the establishment of “Sustainable and Environmental Friendly Campus”. The management of water bodies promotes the coordinated development and management of water, land and related resources, in order to maximise the benefit in term of economic and social welfare in an equitable manner without compromising the sustainability of vital ecosystems. A study on the water quality of Tasik Kejuruteraan of the UKM Bangi campus was carried out to determine the water quality, Water Quality Index (WQI) and its classification according to Interim National Water Quality Standard (INWQS). The purpose of this study was to identify the sources of the water pollution and level of pollution at the lake. The effect of dry and rainy days on the water quality was also evaluated. Parameters selected were pH, temperature, dissolved oxygen (DO), conductivity, turbidity, total suspended solids (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal-nitrogen, lead and cadmium. Temperature, pH, conductivity, dissolved oxygen and turbidity were measured in-situ by using calibrated meters. Heavy metal concentrations were determined by using Atomic Absorption Spectrophotometry (AAS). Methods of sampling and water analyses were performed according to recommendations outlined by the American Public Health Association (APHA). On normal days, the average inflow and outfow of the lake were 0.057 m3s-1 and 0.052 m3s-1 respectively. The theoretical retention time of the lake with mean depth of 1.5 m and an area of 18,000 m2 was 62.5 days. All sampling stations were categorized as Class II i.e. good water quality except station S2, which was categorized as Class III or slightly polluted